Desenvolvimento de compósitos híbridos de epóxi/nanotubos de carbono/cargas minerais e avaliação das propriedades elétricas e termomecânicas: efeito da viscosidade e do solvente - Tokobaro, Paulo Eduardo Asito (2018)
In this research project, epoxy/carbon nanotubes/mineral fillers hybrid nanocomposites were produced using a high energy sonication process. Moreover, two epoxy resins based on DGEBA with different viscosities were used, and the process with solvent (acetone) were carried out. Therefore, the effects of the mineral fillers (montmorillonite, sepiolite and calcium carbonate), acetone and the resin viscosities in the electrical and thermomechanical properties of the nanocomposites were evaluated. The acetone assisted the carbon nanotubes network formation, decreasing the percolation threshold from 0.08 wt% to 0.05 wt% of nanotubes in the higher viscosity epoxy samples. Moreover, the electrical conductivity increased one order of magnitude, raising from 1.15 x 10-5 S/m to 1.94 x 10-4 S/m in the composition with 0.1 wt% of carbon nanotubes. Montmorillonite and sepiolite did not show a sinergistic effect with nanotubes, whereas good results were achieved with calcium carbonate in some compositions. The composition with the higher viscosity resin, 0.1 wt% of carbon nanotubes and 1 wt% of calcium carbonate using acetone reached an electrical conductivity of 1.28 x 10-3 S/m, 1 and 2 orders of magnitude higher than the compositions with 0.1 wt% of carbon nanotubes with and without the use of a solvent, respectively. The lower viscosity resin nanocomposites showed intermediate electrical conductivities if compared to the values of the higher viscosity resin with and without the use of a solvent. The morphology was important in the results, since the nano- and micromectric dispersion together influenced the electrical properties. The nanotubes did not influence the thermomechanical properties, keeping the E’ and Tg values. However, the mineral fillers increased the nanocomposites glass transition temperatures.